Effect of Pineapple Peel Extracts on Organic Fertilizer Nutrients and Growth of Cayenne Pepper (Capsicum Annuum) - Lukhi Mulia Shitophyta; Ratih Dea Larasati; Maharani Nur Bela Pertiwi; Meilya Suzan Triyastuti (Universitas Islam Raden Rahmat, Malang, 2023)
Pineapple peel extract can be used for manufacturing organic fertilizer due to its high content of carbohydrates, protein, and sugar. The study aimed to find the effect of pineapple peel extract on fertilizer nutrients and the growth of cayenne pepper. The experiment employed an experimental method with a Randomized Block Design consisting of three combination pineapple extract treatments. The experiment was performed in 5 L of plastic containers for 15 days. The result showed that pineapple peel extract significantly affected fertilizer nutrients and the growth of cayenne pepper (p < 0.05). The extract of 2500 mL generated the highest height of the plant and the greatest number of leaves. The extract of 2000 mL produced low potassium and nitrogen. Lack of potassium and nitrogen could reduce plant height and change leaf color.